MARAKNYA JUDI ONLINE DAN DAMPAKNYA TERHADAP PENGELOLAAN KEUANGAN DI KALANGAN MAHASISWA (Studi Kasus Pada Mahasiswa Salah Satu Perguruan Tinggi Swasta Di Bandung) - Hatimatunnisani, Hani; Nurfadillah, Haifa; Wasti, Melan; Rika, Putri; Maharani, Risca (Jurnal Sosio dan Humaniora (SOMA), 2023)
Gambling is a criminal act that bets a sum of money where the winner will get all the money that is the subject of the bet. Gambling can harm society and damage the nation's morals. Gambling behavior is sustainable so that it causes curiosity even though it has lost many times, online gambling games carried out by teenagers are the result of social interactions that occur in the environment around them. Social interaction has two sides, namely positive and negative. One example of the negative impact is teenagers who participate in online gambling games.